KONTRIBUSI DAYA LEDAK OTOT TUNGKAI DAN KOORDINASI MATA-KAKI TERHADAP HASIL TENDANGAN KE GAWANG DALAM PERMAINAN SEPAKBOLA SISWA SMA NEGERI 1 SELAT PANJANG - Rizal, Syamsul; Slamet, Slamet; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
ABSTRACT, This study originated from the fact that the lack of mastery of thetechniques of kicking students SMA Negeri 1 Selat Panjang. This is proved from the resultsof field observations. The ability to kick is in need to score goals and win the game. Soresearchers are interested in knowing how big contribution between explosive power legmuscle and eye-foot coordination to kick into the goal in a soccer game SMA Negeri 1Selat Panjang. This type of research is correlational. The population in this study is thewhole student SMAN 1 Selat Panjang which actively participates in the development ofself-sport activities, amounting to as many as 24 students. Samples using total samplingtechnique. Data were collected by using a measurement of the three variables. To measurethe explosive power leg muscle standing broad jump test, and to measure the eye-footcoordination using appropriate target test. While the results of the kick using the test shotson goal. Data were analyzed with Pearson product moment correlation and followed with adouble. The data was analyzed by showing that the first hypothesis there is a meaningfulcontribution between explosive power leg muscle to kick at goal thitung 2226> ttabel 1.72.The second hypothesis there is a meaningful contribution between eye-foot coordination tokick into the goal with thitung 3.320> 1.72 ttabel. The third hypothesis there is a significantrelationship between the explosive power leg muscle and eye-foot coordination jointly tokick into the goal with Fhitung 5332> Ftabel 3:47. It can be concluded that the explosivepower leg muscle and eye-foot coordination has contributed significantly to the results ofkicks at goal.Keywords : explosive power leg muscle, eye-foot coordination, shots on goal